I Am Burnt but Beautiful: Translating Song 1:5a - Bellis, Alice Ogden (Journal of Biblical literature, 2021)
The translation of Song 1:5a as "I am black and beautiful" in the NRSV racializes a passage that is not about race or ethnicity. It is the translator's version of cheap grace. Although the battle against racist language is ongoing, this verse is not the right battleground. Positive images of Africans fill the Hebrew Bible/Tanak/Old Testament, but misleading illustrations, translations, maps, and commentaries obscure them. Rather than misconstruing the plain meaning of Song 1:5a, we should highlight the vital role of Africans in the Bible and expose the cover-up in much past scholarship that minimizes it. The Shulamite is ethnically no different from her Jerusalemite sisters. This verse is more about class distinctions than ethnic or racial ones. Her brothers have forced her temporarily to do work considered lower class due to the sun's harmful effects. Nevertheless, nobody will dictate the terms of beauty, class, or honor and shame to her. Accordingly, a contextual rendering for Song 1:5a is: "I am burnt but beautiful."